2015
DOI: 10.1245/s10434-014-4310-5
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Postoperative Mortality After Esophageal Cancer Resection According to Center Volume: Results from a Large European Multicenter Study

Abstract: The results of this large, multicenter study provide further evidence to support the centralization of esophagectomy to HV centers, with a lower rate of morbidity and better infrastructure to deal with complications following major surgery preventing further mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
81
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 18 publications
8
81
0
2
Order By: Relevance
“…Moreover, it shows that over half of patients with RLNP after esophagectomy did not fully recover during follow-up, and a substantial part (14%) needed a surgical intervention to recover from RLNP. These results stress the importance of preserving the RLN for both short-and long-term outcomes, since several studies have demonstrated that pulmonary complications significantly increase the ICU readmission rate, length of hospital stay and mortality rate, and permanent RLNP after esophagectomy deteriorates quality of life (15,28,29).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, it shows that over half of patients with RLNP after esophagectomy did not fully recover during follow-up, and a substantial part (14%) needed a surgical intervention to recover from RLNP. These results stress the importance of preserving the RLN for both short-and long-term outcomes, since several studies have demonstrated that pulmonary complications significantly increase the ICU readmission rate, length of hospital stay and mortality rate, and permanent RLNP after esophagectomy deteriorates quality of life (15,28,29).…”
Section: Discussionmentioning
confidence: 79%
“…For 6/21 of these patients surgical intervention (medialization thyroplasty) was required. All treatment interventions for vocal cord paralysis were conducted after a median time of 16.5 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] months after esophagectomy. Of all patients that underwent medialization thyreoplasty, 3/6 had no more RLNP symptoms afterwards 2/6 made a partial recovery from their RLNP, and 1/6 did not recover.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…Although higher leak rates have been attributed to low surgical volume [32,33], Hyman et al [34] found that even in a group of high-volume surgeons the leak rates still ranged from 1.6 to 9.9%, despite more surgical experience and high case load. Recently, Penna et al [35] reported on the overall anastomotic failure rate of 15.7% after taTME.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of anastomotic leakage for last 15 years was 15% (19/127) in our hospital; 11% (14cases) of "minor" leakage defined as Grade I and II by the Clavien-Dindo classification (6), and 4% (5 cases) of "major" leakage defined as Grade III or higher. The leakage rate from accumulated data were about 13.3 % according to the National Clinical Database in Japan (7) and 10.2% according to the result of a large European multicenter study (8). According to the report from the STS General Thoracic Surgery Database in the US, the overall leak rate was 10.6%, and mortality after anastomotic leakage was 11.6% (1).…”
Section: Discussionmentioning
confidence: 99%